Incorporation of 5-ethynyl-2'-deoxyuridine (EdU) as a novel strategy for identification of the skewed X inactivation pattern in balanced and unbalanced X-rearrangements - Sisdelli, Luiza; Vidi, Angela Cristina; Moyses-Oliveira, Mariana; Di Battista, Adriana; Bortolai, Adriana; Moretti-Ferreira, Danilo [UNESP]; Dias da Silva, Magnus R.; Melaragno, Maria Isabel; Carvalheira, Gianna (Springer, 2016)
X-chromosome inactivation occurs randomly in normal female cells. However, the inactivation can be skewed in patients with alterations in X-chromosome. In balanced X-autosome translocations, normal X is preferentially inactivated, while in unbalanced X alterations, the aberrant X is usually inactivated. Here, we present a novel strategy to verify the skewed X inactivation pattern through the incorporation of 5-ethynyl-2'-deoxyuridine (EdU) into cells, in 11 patients: five carriers of balanced X-autosome translocations and six of unbalanced X-chromosome alterations. Since EdU is a labeled nucleoside analog of thymidine, its incorporation during DNA synthesis can reveal late replication regions and the inactive X-chromosome. All EdU findings were validated by the human androgen receptor gene (HUMARA) assay. The late replication regions were easily and quickly visualized in all cells, where inactive Xs are marked with strong green fluorescence. It was observed that the normal X-chromosome was preferentially inactivated in patients with balanced X-autosome translocations; while the aberrant X-chromosome was inactivated in most cells from patients with unbalanced alterations. By performing the fluorescence-based EdU assay, the differences between the active and inactive X-chromosomes are more easily recognizable than by classic cytogenetic methods. Furthermore, EdU incorporation allows the observation of the late replication regions in autosomal segments present in X derivatives from X-autosome translocations. Therefore, EdU assay permits an accurate and efficient cytogenetic evaluation of the X inactivation pattern with a low-cost, easy to perform and highly reproducible technique.